2003
DOI: 10.1007/s10311-003-0033-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of 3,4-dichloroaniline and 2,4,6-trinitrotoluene in soil in the presence of natural adsorbents

Abstract: The use of some adsorbents may decrease the toxicity of organic pollutants to microbes and plants during soil bioremediation. Experiments were conducted with 3,4-dichloroaniline (DCA) and 2,4,6-trinitrotoluene (TNT). Here we demonstrate that activated carbon can reduce the toxicity of readily available chemicals in soil by transferring them to a less available fraction. This process results in accelerated biodegradation of dichloroaniline by the inoculated Paracoccus denitrificans st. 3XA. In the case of TNT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Sorbents serve as a source of nitrogen and phosphorus and a place of localization of microorganisms-destructors, and they increase the moisture capacity and aeration of soils [ 22 ]. Studies carried out earlier in the central region of Russia made it possible to create an effective method of the sorption-biological treatment of soils contaminated with organic pollutants [ 23 , 24 , 25 , 26 , 27 ]. The use of granular activated carbon (GAC) can accelerate the processes of the bioremediation of soils contaminated with diesel fuel, used engine oil, and petroleum [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sorbents serve as a source of nitrogen and phosphorus and a place of localization of microorganisms-destructors, and they increase the moisture capacity and aeration of soils [ 22 ]. Studies carried out earlier in the central region of Russia made it possible to create an effective method of the sorption-biological treatment of soils contaminated with organic pollutants [ 23 , 24 , 25 , 26 , 27 ]. The use of granular activated carbon (GAC) can accelerate the processes of the bioremediation of soils contaminated with diesel fuel, used engine oil, and petroleum [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…В работах [13,14] предлагается использовать метод сорбционной биоремедиации, в основе которого лежит внесение оптимальных доз натуральных сорбентов. С их помощью достигается снижение токсичности почв по отношению к микроорганизмам и растениям за счет сорбции загрязнителя и улучшение структуры почвы.…”
Section: оригинальная статьяunclassified
“…This observation could be due to the fact that PPAC acted as an adsorbent in the soil as well as cometabolic carbon substrate while the NPK fertilizer provided inorganic nutrients to the autochthonous microorganisms in the soil. Enhanced bioremediation of soil highly contaminated with herbicide propanil (3',4'-dichloropropionanilide) in the Krasnodar region of Russia, 3,4-dichloroaniline, polychlorinated biphenyls (PCB) and 2,4,6-trinitrotoluene (TNT) in the presence of activated carbon have been reported [48][49][50][51][52]. Accelerated biodegradation of anthracene in the presence of groundnut shellderived activated carbon has been reported by Owabor and Aluyor [28] while Lou et al [53] have also observed accelerated biodegradation of pentachlorophenol in soil in the presence of bamboo biochar.…”
Section: Effect Of Amendment Agents On Natural Attenuationmentioning
confidence: 99%